Compilation of Islamic Law on Underage Marriage in Javanese Ethnic Communities in Lingga Bayu Mandailing Natal - Aswar Habibi (International Journal Ihya' 'Ulum al-Din, 2022)
This study aims to analyze the habits of underage marriage in Lingga Bayu Mandailing Natal, especially those carried out by the Javanese ethnic community. This study explores the rights and obligations according to the compilation of Islamic law, which looks at how consistent the perpetrators of underage marriages are in fulfilling their rights and responsibilities in the household. This research is field research with research subjects, namely the perpetrators of underage marriages who are Javanese in the Lingga Bayu District. Data collection techniques used are observation, interviews, and documentation. From this, the results of this study indicate that the perpetrators of underage marriages are closely related to their rights and obligations, which are closely tied to the compilation of Islamic law. The marriages below are generally accepted and understood by Muslims who are 'experts' of Islamic law and are educated but not by the general public. As a follow-up, in reaching this understanding, the perpetrators of underage marriages need to understand the rights and obligations of husband and wife, especially regarding the leadership or control of the household in the hands of the husband. Meanwhile, a wife should obey her husband as long as it is within limits justified by religion.